Kenaf fibre reinforced cementitious composites - Noor Abbas, Al-Ghazali; Abdul Aziz, Farah Nora Aznieta; Abdan, Khalina; Mohd Nasir, Noor Azline; Norizan, Mohd Nurazzi (Multidisciplinary Digital Publishing Institute, 2022)
Increased environmental awareness and the demand for sustainable materials have promoted the use of more renewable and eco-friendly resources like natural fibre as reinforcement in the building industry. Among various types of natural fibres, kenaf has been widely planted in the past few years, however, it hasn’t been extensively used as a construction material. Kenaf bast fibre is a high tensile strength fibre, lightweight and cost-effective, offering a potential alternative for reinforcement in construction applications. To encourage its use, it’s essential to understand how kenaf fibre’s properties affect the performance of cement-based composites. Hence, the effects of KF on the properties of cementitious composites in the fresh and hardened states have been discussed. The current state-of-art of Kenaf Fibre Reinforced Cement Composite (KFRCC) and its different applications are presented for the reader to explore. This review confirmed the improvement of tensile and flexural strengths of cementitious composites with the inclusion of the appropriate content and length of kenaf fibres. However, more studies are necessary to understand the overall impact of kenaf fibres on the compressive strength and durability properties of cementitious composites.